Activity of Platinum/Carbon and Palladium/Carbon Catalysts Promoted by Ni2P in Direct Ethanol Fuel Cells. Issue 12 (22nd October 2014) - Li, Guoqiang; Feng, Ligang; Chang, Jinfa; Wickman, Björn; Grönbeck, Henrik; Liu, Changpeng; Xing, Wei
Abstract Ethanol is an alternative fuel for direct alcohol fuel cells, in which the electrode materials are commonly based on Pt or Pd. Owing to the excellent promotion effect of Ni2P that was found in methanol oxidation, we extended the catalyst system of Pt or Pd modified by Ni2P in direct ethanol fuel cells. The Ni2P‐promoted catalysts were compared to commercial catalysts as well as to reference catalysts promoted with only Ni or only P. Among the studied catalysts, Pt/C and Pd/C modified by Ni2P (30 wt %) showed both the highest activity and stability. Upon integration into the anode of a homemade direct ethanol fuel cell, the Pt‐Ni2P/C‐30 % catalyst showed a maximum power density of 21 mW cm−2, which is approximately two times higher than that of a commercial Pt/C catalyst. The Pd‐Ni2P/C‐30 % catalyst exhibited a maximum power density of 90 mW cm−2. This is approximately 1.5 times higher than that of a commercial Pd/C catalyst. The discharge stability on both two catalysts was also greatly improved over a 12 h discharge operation.